A final report on the practice in industry training in fish capture - Galang, Ruperto R., Jr. (Miagao, Iloilo Colelge of Fisheries, University of the Philippines, 1977)
This report comprises the observations and data whwich I gathered during my practice in industry training in the second semester of the school year 1974-1975. Most of the fishing gears that we have observed were generally capital intensive, making them subversive to the sustenance fisherman. It includes the description of the gear, the method of operation and of course the economics. e.i. Capital investment, operational expenses and the different types of sharing practiced in the industry. The areas that we covered were, the island of Panay, where we surveyed the set0het, the baklad and the tuna long line, in Libertad, Antique, the purse seine was in Burias Island, the baby trawl in Navotas and the Beach seine in Tobaco, Albay. Considering the limited time allotted to each gear, very satisfactory observations, comments and recommendations cannot be given here. Nevertheless, it is my fervent hope that this report will in one way or another achieve it aims. I observed that a great number of sustenance fishermen still cling to methods of fishing which have already, deep sea fishing which have already been proven to be inadequate. Evolutionary speaking, deep-sea fishing is synonymous to hunting which implies that it is more primitive than aquaculture. On the other hand the investments incurred in deep-sea fishing involves more capital, thereby making it, as I have said, subversive to the common people. One possible solution to this problem is through the cooperative system. In this system, the meager sources of the people can be pooled together in order to procure the necessary materials in order to engage in deep-sea fishing.
Report on practice in industry training in fish capture submitted to the College of Fisheries, University of the Philippines in partial fulfillment of the requirement of the requirements for graduation in fish capture.
Keywords: Fish capture